2016
DOI: 10.3109/10717544.2016.1153748
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, toxicological and neuronal localization assessment of galantamine/chitosan complex nanoparticles in rats: future potential contribution in Alzheimer’s disease management

Abstract: Purpose: Nasal galantamine hydrobromide (GH)/chitosan complex nanoparticles (CX-NP2) could have an improved therapeutic potential for managing Alzheimer's disease (AD). The current study aimed to investigate if the complexation reaction between GH and chitosan altered the pharmacological and toxicological profiles of the parent drug; GH. Methods: The nasal administration of CX-NP2 to male Wistar rats for 12 consecutive days was compared to negative control group, and oral and nasal GH solutions treated groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 57 publications
(78 reference statements)
0
30
0
Order By: Relevance
“…The chitosan complexes were used to encapsulate galantamine, a drug used to manage mild to moderate Alzheimer’s disease. This study showed no toxicity or histopathological signs and decreased the level of AChE protein and activity in the brains of rats (Hanafy et al 2016). The efficacy and safety of these gelatin nanoparticles make them a promising candidate in future research of nasally delivered drugs.…”
Section: Biodegradable Nanoparticlesmentioning
confidence: 61%
See 1 more Smart Citation
“…The chitosan complexes were used to encapsulate galantamine, a drug used to manage mild to moderate Alzheimer’s disease. This study showed no toxicity or histopathological signs and decreased the level of AChE protein and activity in the brains of rats (Hanafy et al 2016). The efficacy and safety of these gelatin nanoparticles make them a promising candidate in future research of nasally delivered drugs.…”
Section: Biodegradable Nanoparticlesmentioning
confidence: 61%
“…These nanoparticles are of particular interest because they possess the capability to cross mucus membranes, specifically the nasal cavity and intestinal tract, as they are able open tight junctions of epithelial cells (Vila et al 2002, Grabowski et al 2015). Due to chitosan’s unique ability to cross mucus membranes, a 2016 study utilized the nasal administration of chitosan nanoparticles (Hanfy et al 2016). The chitosan complexes were used to encapsulate galantamine, a drug used to manage mild to moderate Alzheimer’s disease.…”
Section: Biodegradable Nanoparticlesmentioning
confidence: 99%
“…For example, it was confirmed that intranasal administration of galantamine NPs did not lead to histopathological manifestations in the olfactory-bulb, neither in other brain regions including the orbitofrontal cortex, parietal cortex or hippocampus. Furthermore, orbitofrontal cortex neurons also exhibited intact nuclear membrane, mitochondria as well as endoplasmic reticulum after the uptake of chitosan-GAL NPs [ 42 , 50 ]. Aside using biodegradable and biocompatible polymers to build nanocarriers of AD therapeutics, special attention has to be paid to synthetize the NPs without using toxic additives, surfactants or solvents.…”
Section: Discussionmentioning
confidence: 99%
“…With the intention of reducing side-effects of galantamine, Hanafy and coworkers encapsulated the API in chitosan NPs by inotropic gelation [ 42 , 50 ]. The chitosan-GAL nanoformula was administered to male Wistar rats intranasally (3 mg/kg/day).…”
Section: Use Of Chitosan Nanoparticles In the Treatment Of Alzheimmentioning
confidence: 99%
“…The cationic surface of chitosan nanoparticles is responsible for the mucoadhesive properties of the chitosan-based nanocarriers that facilitate the retention in the site of interest, thus providing a sustained release of the encapsulated drug. For this reason chitosan nanoparticles are considered very promising candidates for the Alzheimer treatments through intra-nasal administration [144,145].…”
Section: Nanoparticles and Alzheimer' Diseasementioning
confidence: 99%